2020
DOI: 10.1186/s12886-019-1288-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intraocular pressure measured by ocular response analyzer and Goldmann applanation tonometer after corneal refractive surgery: a systematic review and meta-analysis

Abstract: Background Accurate measurement of intraocular pressure (IOP) after corneal refractive surgery is of great significance to clinic, and comparisons among various IOP measuring instruments are not rare, but there is a lack of unified analysis. Although Goldmann Applanation Tonometer (GAT) is currently the internationally recognized gold standard for IOP measurement, its results are severely affected by central corneal thickness (CCT). Ocular Response Analyzer (ORA) takes certain biomechanical pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…IOPcc is less affected by corneal properties as a CCT independent IOP measurement. 49 Ehrlich et al showed better sensitivity and specificity to identify glaucoma using IOPcc compared with GAT. Applying an optimal GAT threshold at 20.9 mmHg, GAT showed area under curve (AUC) = 0.78, while using an IOPcc threshold at 18.4 mmHg, IOPcc showed AUC = 0.93, p<0.001.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IOPcc is less affected by corneal properties as a CCT independent IOP measurement. 49 Ehrlich et al showed better sensitivity and specificity to identify glaucoma using IOPcc compared with GAT. Applying an optimal GAT threshold at 20.9 mmHg, GAT showed area under curve (AUC) = 0.78, while using an IOPcc threshold at 18.4 mmHg, IOPcc showed AUC = 0.93, p<0.001.…”
Section: Discussionmentioning
confidence: 99%
“…Among IOPcc, IOPg, and GAT, exactly which value would be the best to represent the true IOP is still under debate. [47][48][49] The gold standard of IOP measuring is the GAT, whose accuracy is limited when applied in out-ofthe range central corneal thickness (CCT), for example, in post-refractive surgery and thinner or thicker than normal average CCT. IOPcc is less affected by corneal properties as a CCT independent IOP measurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with GAT, ORA has been demonstrated to significantly overestimate the IOP values, especially at high IOP levels [ 47 , 48 ]. Several authors have demonstrated that the IOPcc is less affected by corneal properties [ 48 , 49 , 50 , 51 ] and may better reflect the true IOP after refractive surgery of the cornea when compared to GAT IOP values [ 52 ].…”
Section: Non-contact Tonometry (Air-puff Tonometry)mentioning
confidence: 99%
“…IOP should be tested by the same, individually adjusted and well-tolerated devices during follow-up of MPSs patients since different tonometry methods may result in variable IOP-values. Goldmann applanation tonometry, the gold standard for IOP measurement, was less dependent on corneal properties, making it more reliable for measuring IOP of patients with MPSs [55]. Ocular response analyzer and iCare rebound tonometer were tested and proved to be attractive alternatives to applanation tonometry in MPS patients [54].…”
Section: Diagnosis Of Glaucoma In Mpssmentioning
confidence: 99%